2021
DOI: 10.4103/jfmpc.jfmpc_397_21
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits, diversity, and predictors among pregnant women attending primary health care centers for antenatal care in Lagos, Nigeria

Abstract: Background and Aim: Inadequate nutrition during fetal development resulting from poor dietary habits leads to reprogramming within fetal tissues and poses as a risk factor for non-communicable diseases in later life. This study was conducted to determine the dietary habits, diversity, and predictors among pregnant women in Lagos, Nigeria. Methods: A descriptive cross-sectional study was conducted using a structured interviewer-administered questionnaire to obtain data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
3
7
1
Order By: Relevance
“…Sharing food among family members, could lead to a shortage of food within the household, and women usually prioritize their children, limiting their diversified dietary consumption 37 . This finding was similar to results obtained from Nigeria 32 . Related to this, women with extended families (≥ 5) had a higher susceptibility to a less diversified diet.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Sharing food among family members, could lead to a shortage of food within the household, and women usually prioritize their children, limiting their diversified dietary consumption 37 . This finding was similar to results obtained from Nigeria 32 . Related to this, women with extended families (≥ 5) had a higher susceptibility to a less diversified diet.…”
Section: Discussionsupporting
confidence: 92%
“…Higher estimates were also reported from India (18%) 23 , Nepal (45%) 31 , Nigeria (30.8%) 32 , Southern Ethiopia (7.9%) 33 , and Eastern Ethiopia (43%) 34 . The possible explanation for this discrepancy in magnitude might be due to study period differences and geographical and socio-cultural differences that could affect availability and access to food.…”
Section: Discussionmentioning
confidence: 85%
“…The women from households with greater monthly incomes had lower odds of having sub-optimal dietary diversity in comparison to women with lesser monthly income, a finding that corroborates what had been previously reported. 19 , 48 , 49 Household food insecurity had a strong association with women’s dietary diversity in this study. The participants were categorized into food secure, mild, moderate and severe food-insecure households but the last two categories were merged for the analysis due to few numbers of subjects under them.…”
Section: Discussionmentioning
confidence: 46%
“…In terms of DK, our findings were similar to those of studies conducted in Sudan [ 22 ] and Iran [ 23 ] where more than half of the participants with T2D had good DK levels. A different pattern of results was observed in the Kingdom of Saudi Arabia (KSA) [ 18 ], Jordan [ 10 ], and Nigeria [ 11 ] where subjects demonstrated poor DK. The difference in knowledge levels among these populations with T2D may be attributable to the different knowledge assessment tools, study designs, and sociocultural differences between these populations.…”
Section: Discussionmentioning
confidence: 99%
“…Also, knowledge of diabetes was found to be associated with compliance with treatment and a decrease in complications [ 9 ]. In Jordan [ 10 ] and Nigeria [ 11 ], studies reported poor dietary knowledge (DK) levels in the population with T2D, thus hindering diabetes outcomes. In Lebanon, studies showed that patients' knowledge and practice scores related to diabetes' self-management were unsatisfactory [ 12 ].…”
Section: Introductionmentioning
confidence: 99%